Seroprevalence and Incidence of Chlamydia Trachomatis on Sperm Quality in Men of Procreating Age in Brazzaville - Roland M0UKALA, David Charles; AH0MB0, Gabriel; AMPA, Raoul; SILOU MASSAMBA, Jacques François; NGUIMBI, Etienne; K0MB0, Yvon Sévérin (International Journal of Innovative Research in Medical Science, 2021)
Chlamydia trachomatis is responsible for male infertility. The mechanism of action of C. trachomatis on male reproductive function is still controversial. The present study aims to evaluate seroprevalence and its influence on sperm quality in a male sample of 307 patients requesting serological examination for C. trachomatis, 73 of whom were examined by sperm analysis - spermocytogram and sperm culture. The patients were aged between 17 and 71 years, consulting for infertility or urology. The analysis of C. trachomatis serologies, based on the enzyme immunoassay dosage of immunoglobulin G, yielded 111 cases of positive serology, i.e. a seroprevalence of 36.2%. The age group over 60 years of age, the least represented group, had the highest frequency at 52.9%. Analysis of the 73 spermograms and spermocytograms revealed a non-significant difference in mean sperm concentration, 49.67 million sperm per milliliter, standard deviation ±45.71, in Chlamydia negative subjects versus 7.66 million sperm per milliliter, standard deviation ±10.98, in Chlamydia positive subjects. A non-significant change in total motility of 39.83%, standard deviation ±27.49, in Chlamydia-negative subjects versus 36.03%, standard deviation ±24.58, in Chlamydia-positive subjects, a 3% drop. Abnormal sperm forms, 51.86%, standard deviation ±19.60, in Chlamydia negative versus 57.17%, standard deviation ±21.41, in Chlamydia positive, an increase of 6%. The global reading of the average spermogram of Chlamydia positive individuals revealed oligospermia and asthenospermia as abnormalities. This suggests that there is a possible link between C. trachomatis infection and decreased sperm quality in Chlamydia positive patients.